THE IMPORTANCE OF USING ARTIFICIAL INTELLIGENCE AND MACHINE LEARNING FOR THE DEVELOPMENT OF THE COVID-19 VACCINE: AN INTEGRATIVE REVIEW (REMUNOM, 2026)
The COVID-19 pandemic demanded rapid scientific responses, driving the use of Artificial Intelligence (AI) and Machine Learning (ML) in vaccine development. This study consists of an integrative literature review aimed at analyzing the importance, safety, and role of these technologies in the COVID-19 vaccination process. The search was conducted in the BVS, SciELO, and Google Scholar databases, including articles published between 2020 and 2025. The results show that AI and ML contributed to accelerating research and development stages, optimizing genetic sequences, identifying molecular targets, and adapting to viral variants, in addition to supporting safety and logistics analyses. Despite the advances, ethical, technical, and regulatory challenges persist, especially related to data quality, algorithmic biases, and privacy protection. It is concluded that AI and ML represent strategic tools for innovation in vaccinology and for strengthening the response to future health emergencies.